1994
DOI: 10.1098/rsta.1994.0080
|View full text |Cite
|
Sign up to set email alerts
|

Self-order in flexible non-mesogenic macromolecules

Abstract: Some very flexible linear poly(di-n-alkylsiloxane)s and cyclolinear oligo- and polyorganosiloxanes, which do not contain classical rigid rodlike or disclike mesogens, similar to other semi-organic polymers like polyphosphazenes and polysilanes, can form thermodynamically stable two-dimensionally ordered thermotropic mesophases. In many respects the mesophases in polysiloxanes resemble columnar liquid crystals which seems to be the result of the amphiphilic constitution of the polyorganosiloxanes. The origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The reason that our compressed PDES networks did not transform into the mesophase can be understood from the mesophase microstructure. The mesophase has a columnar structure in which the Si−O chain backbones align in a common direction (the axes of the columns) . In uniaxial extension, the mesophase can form because the chains are stressed in a common direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason that our compressed PDES networks did not transform into the mesophase can be understood from the mesophase microstructure. The mesophase has a columnar structure in which the Si−O chain backbones align in a common direction (the axes of the columns) . In uniaxial extension, the mesophase can form because the chains are stressed in a common direction.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in properties between PDES and PDMS is due to the difference in segment−segment interactions in the two polymers. It has been suggested that segment alignment is energetically favorable in PDES because overlap of ethyl groups on neighboring chain segments is maximized when the siloxane backbones are oriented in a common direction. ,, The orientational enthalpic coupling between segments in PDES arises as nonpolar ethyl groups associate with each other in preference to the polar Si−O backbone. Alignment of the chain backbones decreases the internal energy of the network, a result that has been verified by calorimetric measurements. ,, For the mesophase transition to be spontaneous, this favorable decrease of internal energy must offset the entropic penalty for alignment.…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of the mesophase in PDES in 1975 stimulated characterization of this polymer by DSC, optical and electron microscopy, X-ray diffraction, NMR, and other techniques in order to understand the mesophase structure and its relation to the crystalline polymorphs. The crystal−mesophase transition observed on heating at sub-RT temperatures gives samples with almost 100% mesophase content. ,,, The comparison of the PDES density in the mesophase with the theoretical crystallographic density showed 7 that the chain packing in this phase can be described by a monoclinic unit cell, which slightly differs from the hexagonal packing. Polarized optical microscopy revealed a formation of extended lamellar structures in the mesophase obtained by slow cooling of the melt …”
Section: Introductionmentioning
confidence: 99%
“…The cyclolinear polysiloxanes have bulk columnar liquid crystal phases, and it has been proposed that the multilayers form by a sliding mechanism . In order to understand the mechanism of collapse better and to examine the validity of this model, we have studied the collapse of monolayers of a cyclolinear polysiloxane by several methods.…”
Section: Introductionmentioning
confidence: 99%